A ciência das bolhas de sabão no ensino médio : uma abordagem multidisciplinar - Martins, Magda Melo Borges (2016)
This work aims the inclusion of multidisciplinary approach in high school physics classes, through the study of soap bubble. The multidisciplinary approach proportioned from studies of soap bubbles is justified, because for unravel the science behind these bubbles is necessary treat simultaneously physical phenomena, chemical and biological that explain its production, thickness and coloration, as well as the mathematics that explains why the bubbles are always spherical. The choice of soap bubble is also justified by provide motivation to students who usually are enchanted by its beauty, and by scientifically explain something seemingly trivial however is part of their lives at an early age. The work consists of the development of teaching materials theoretical and experimental that should be used in the classroom, in addition the story of this application and considerations about how the multidisciplinary experience may have contributed to the teaching learning process in physics. The project was developed in one class of third year high school, in Colégio Estadual Professora Olga Mansur, Goiânia/GO. Based on the application of the teaching material we can conclude that we have achieved improvements in the teaching process in physics, the material prepared aroused the students' interest in topics related to science and it provided to teachers and students more dynamic physics classes, attractive and meaningful.